Urban food environments in Africa: implications for policy and research. Issue 4 (28th January 2019) - Holdsworth, Michelle; Landais, Edwige
Abstract : Africa is currently experiencing rapid urbanisation impacting on people's food environments and dietary habits. Such changes are associated with higher prevalence of obesity coexisting with undernutrition. The present paper provides an overview of the healthiness of African urban food environments. We discuss the ways that food environments can be characterised and summarise the methods that can be used to investigate and intervene in the food environment. Data for Africa over a 50-year period (1961–2013) suggest an increasing availability of energy, animal products, fruit and vegetables, vegetable oils, sugar and sweeteners but a decrease in animal fats. There is a lack of evidence about how social, physical and macro-environments drive dietary habits in urban Africa, as most research has focused on the individual level. Examining how food consumption is embedded in everyday life, by investigating social environments is crucial to developing effective interventions. The informal food sector plays an important role in the retail food environment. Macro-level food price changes are an important factor influencing nutritional quality of African diets. The rapid expansion of food/beverages advertising in Africa threatens traditional food habits. Liberalisation of food trade is already impacting on the nutritional quality of food available. Improving African food environments represents a pressing public health concern and has the potential to prevent all forms of malnutrition. Hence, by conducting research into the role of urban social, physical and macro-environments, emerging interventions and policies are likely to positively impact on nutritional status, thereby enhancing social and economic development.